Design and challenges of an autonomous ship alarm monitoring system for enhanced maritime safety - Oumaima Bouanani; Sara Sandabad; Abdelmoula Ait Allal; Moulay El Houssine Ech-Chhibat (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
Maritime transportation holds the largest share of global trade, but the rising operational costs - particularly those associated with human resources - pose significant challenges to the industry. Coupled with this, the shortage of skilled seafarers and the prevalence of human error, which accounts for 59.1% of maritime accidents, threaten the sector's sustainability. The shift towards autonomous ships presents a promising alternative for enhancing operational efficiency and safety while reducing reliance on onboard human crews. Autonomous vessels, controlled remotely by shore-based engineers, require robust systems for effective and safe operation. One critical component of such systems is the autonomous ship alarm monitoring system, essential for managing the complex array of alarms that ensure the safety and functionality of ship operations. This paper examines the challenges posed by the increasing complexity of ship control systems and the necessity of enhanced automation. Through an in-situ study across various merchant ships, the criticality and response time of alarms were evaluated, leading to a structured approach for engineer responsibilities and response strategies. The findings contribute to a proposed concept for an efficient, autonomous alarm management system, addressing both technical and operational needs to support maritime sustainability.